2022
DOI: 10.1088/1755-1315/974/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical properties of various ages oil palm plantation in Ultisols of Bengkulu

Abstract: Oil palm plantation (OPP) expands to soil with less suitable including Ultisol. The purposes of this study were (1) to compare some selected soil properties among various OPP ages and (2) to determine the correlation among the selected soil properties. A Completely Randomized Block Design with single factor treatments of oil palm age consisting of 2-yr, 3 -yr, 4-yr, 8-yr, and 32-yr of OPP, and all treatments was repeated three times. Blocking was based on the OPP floor positions: circle weeding (CW), frond sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…And also suggest that soil degradation is more severe in oil palm plantations than in rubber plantations [ 46 ]. Recently, Prawito et al [ 21 ] suggest that proper management and improving soil SOC with the maintenance of undergrowth vegetation can achieve soil sustainability and shown the understory vegetation biomass, weight, and density decreased with the increasing age of the plantations compared with young plants of 4 years of age [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And also suggest that soil degradation is more severe in oil palm plantations than in rubber plantations [ 46 ]. Recently, Prawito et al [ 21 ] suggest that proper management and improving soil SOC with the maintenance of undergrowth vegetation can achieve soil sustainability and shown the understory vegetation biomass, weight, and density decreased with the increasing age of the plantations compared with young plants of 4 years of age [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, by nature, the roots become intertwined and generate soil compaction that hence forth in increasing the bulk density of the soil [ 19 ]. Instead, studies have shown that differences in the ages of oil palm plots cause changes in soil properties and marked differences in the soil degradation [ 21 ]. For example, Guillaume et al [ 22 ] reported a lower carbon content, lower nitrogen, and higher bulk density under oil palms compared with under rubber trees.…”
Section: Introductionmentioning
confidence: 99%
“…However, by nature, the roots become intertwined and generate soil compaction that hence forth in increasing the bulk density of the soil (Salamat et al, 2021). Instead, studies have shown that differences in the ages of oil palm plots cause changes in soil properties and marked differences in the soil degradation (Prawito et al, 2022). For example, Guillaume et al (2018) reported a lower carbon content, lower nitrogen, and higher bulk density under oil palms compared with under rubber trees.…”
Section: Introductionmentioning
confidence: 99%